Pengamatan Laju Penyakit White Syndrome Pada Montipora sp. Di Pulau Pramuka, Taman Nasional Laut Kepulauan Seribu, DKI Jakarta - Rosyid, Abdur; Luthfi, Oktiyas Muzaky (Journal of Marine and Aquatic Sciences; Vol 5 No 1 (2019), 2018)
Coral disease now became main factor of coral degradation in the world. There is still a few report about coral disease in Kepulauan Seribu Marine National Park (TNKPS) include of white syndrome (WS) in Montipora sp. WS was characterized by white area on coral surface at several stages. WS had caused coral tissue loss and leaved bare CaCO 3 skeleton that was caused by pathogenic Vibrio coralliitycus associated with other microorganisms. In this study the progress of WS calculated by measurement of the distances of WS that moved from diseased to healty coral surface. All calculations was performed used ImageJ Software. Our result showed that WS progression rate in first week was 9.06 cm 2 and the second week was 2.37 cm 2 . Total coral tissue mortality was 12.03% for 2 weeks.